1970
DOI: 10.4314/sajas.v46i3.8
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of genotype, housing and dietary calcium in layer performance, eggshell quality and tibia characteristics

Abstract: The study was designed to evaluate the interactions in performance, eggshell quality and tibia traits of two laying hen genotypes, namely a commercial hybrid, Lohmann (LSL), and a traditional breed, the Czech Hen (CH), housed in conventional cages and on litter, and fed two levels of dietary calcium (Ca) (3.5% vs. 3.0%). A significant interaction between genotype, housing and Ca was determined in egg weight. The heaviest eggs were laid by LSL hens housed in cages and fed 3.0% Ca (61.8 g), and the lightest laid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
2
2
Order By: Relevance
“…Although there was a strong genetic background of growth in broilers, the difference in free-range and intensive CFG might be because of the continuous availability of commercial feed and better growth in the intensive environment. However, the aforementioned findings differ from those from laying hens where it was reported that genotype did not affect the tibia weight (Tůmová et al, 2016). However, the present results confirm those of Tůmová et al (2016) relative to effects of housing system on tibia weight in layers.…”
Section: Resultscontrasting
confidence: 74%
See 2 more Smart Citations
“…Although there was a strong genetic background of growth in broilers, the difference in free-range and intensive CFG might be because of the continuous availability of commercial feed and better growth in the intensive environment. However, the aforementioned findings differ from those from laying hens where it was reported that genotype did not affect the tibia weight (Tůmová et al, 2016). However, the present results confirm those of Tůmová et al (2016) relative to effects of housing system on tibia weight in layers.…”
Section: Resultscontrasting
confidence: 74%
“…However, the aforementioned findings differ from those from laying hens where it was reported that genotype did not affect the tibia weight (Tůmová et al, 2016). However, the present results confirm those of Tůmová et al (2016) relative to effects of housing system on tibia weight in layers.…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…Similarly, previous studies also documented greater eggshell thickness in eggs from non-cage systems and outdoor layers as compared to the caged conventional system [7,[49][50][51]56]. In contrast, some studies demonstrated a higher shell thickness in eggs from cages as compared to the cage-free systems, while others showed no interaction between the housing systems and eggshell thickness [48,57]. These different outcomes between studies might be due to the interaction of genotype and housing system or to differences in the age of the laying hens.…”
Section: Discussionmentioning
confidence: 82%